Electrical characteristics of flexible amorphous indium–tin–gallium–zinc oxide thin-film transistors under repetitive mechanical stress. (25th August 2021) - Lee, Hosang; Cho, Kyoungah; Kong, Heesung; Lee, Seungjun; Lim, Junhyung; Kim, Sangsig
Abstract: In this study, we investigated the effect of repetitive mechanical stress on the electrical characteristics of amorphous indium–tin–gallium–zinc oxide (a-ITGZO) thin-film transistors (TFTs). The degradation of the electrical characteristics of an a-ITGZO TFT with a curvature radius of 2 mm is minimal even after the TFT undergoes bending 10 5 times. Our technology computer-aided design simulation reveals that the electrical characteristics degraded by the repeated bending cycles are due to the increase in the acceptor-like Gaussian states ( N GA ) related with the generation of oxygen interstitial defects.